Nekateri alternativni načini ocenjevanja znanja pri športni vzgoji - Kovač, Marjeta (Šport (Ljubljana), 2016)
Assessment is one of the most difficult and complex issues that physical education teachers face. Traditional approaches to assessment are still dominating but alternative approaches to assessment are appearing among PE teachers. According to the constructivist perspective of learning, pupilćs learning is considered to be an active, developmental, and multi-layered process, which means that teaching should be such a process as well. A teacher should develop various aspects of the knowledge, processes and skills and adapt different approaches to assessment. This article explains some of the concepts that appear in the contemporary context of evaluation, and presents some examples of alternative approaches, on the case of various sporting activities. Such evaluation is based on the use of authentic tasks, evaluation of conceptual knowledge, involvement in student self-assessment and self-evaluation. Such a process has diagnostic and formative role and provides knowledge of higher quality, because the feedback encourages students to remain involved in sporting activities.
Keywords: alternative assessment; alternativno ocenjevanje; authentic assessment; avtentično ocenjevanje; constructivist approach; konstruktivistični pristop; physical education; sport; šport; športna vzgoja